Spontaneous uterine rupture in unscarred uterus in a low resource setting in India: A case series - Chowdhury, Pushpal (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Uterine rupture, a critical event during childbirth, poses significant challenges in familial and societal contexts. Despite concerted efforts to prevent such occurrences, inevitabilities arise, placing immense burdens on emergency healthcare teams, particularly in remote areas with inadequate facilities. What makes uterine rupture even more dangerous is the difficulty and the delay in diagnosis, especially in the unscarred uterus which invariably causes loss of the fetus in vivo and a high degree of maternal morbidity and mortality. This case series described three cases of rupture in the unscarred uterus, and their subsequent management and outcomes in a resource-constrained environment in Northeast India. Out of three cases, neonatal mortality was reported in all the cases, while maternal mortality was reported in one case. The findings underscore the critical need for heightened awareness, efficient diagnostic strategies, and improved healthcare infrastructure to address the complexities of uterine rupture in unscarred uteri, particularly in low-resource settings.